Qur'anic Hermeneutics and its Applications by Fazlur Rahman - Rozaq, Abd. (Nursyam Center, 2023)
This article seeks to identify the ideas of Fazlur Rahman, a classical thinker who is also ultramodern and advances neo modernism. Muslims are required to have a critical understanding of the Western world. One of his contributions is the Double Movement hermeneutic technique. This technique has distinct properties that can be used to understand legal and social texts. To identify Fazlur Rahman's views, the literature research approach is performed. According to the findings, Rahman emphasized the need of knowing the socio-historical backdrop in the field of law. Rahman was crucial in the development of a more methodical interpretive building. Even though his method is not wholly novel, he made an important contribution by emphasizing socio-historical factors and the Double Movement approach. However, problems and flaws in his technique are still being contested among Muslim academics. This article discusses the benefits and drawbacks of this strategy, presenting a fair picture of Rahman's contribution to ultramodern Islamic thinking.